The effect of perceived usefulness, perceived ease of use, trust, attitude and satisfaction into continuance of intention in using Alipay / Florentina Kurniasari, Nadiah Abd Hamid and Chen Qing hui - Kurniasari, Florentina; Abd Hamid, Nadiah; Chen, Qing hui (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
The rapid development of information and communication technology is happening in various lines of businesses including the financial sector. As one of the most popular mobile payment channel in China, Alipay faces a tough competition from its rival, WeChat. Security and fraud have become serious issues for customers in using mobile payment channels. There was a decrease in the number of Alipay users due to these issues. The objective of this paper was to examine the effect of Perceived Usefulness, Perceived Ease of Use, Trust and Satisfaction on Continuance of Intention of consumers in using the Alipay mobile application. Quantitative methods were used to test the hypotheses. Questionnaires were distributed among Chinese residents who have used the Alipay application. Data was analyzed using the SEM with the SmartPLS. The result of the study showed that only perceived usefulness did not have any positive effect on attitude. Meanwhile, the other variables such as perceived ease of use and trust had a positive effect on attitude. Furthermore, the attitude variable also had a positive effect on user satisfaction with the satisfaction having the strongest effect towards continuance intention in using the Alipay application.